Analisis Manajemen Perpustakaan Sekolah di SMAN 1 Janapria - Samsul Rizal; Mul Muliadi (Peneliti.net, 2021)
School library as a provider of science and information has a significant role to educational institutions. The school library is a resource center for science and information residing in schools, both basic and intermediate levels. School libraries should be able to play a role, especially in helping students to achieve educational goals. For this purpose, school libraries need to realize their vision, mission and goals by preparing adequate librarians, collections and quality. By maximizing the role and function of management, it is expected that the school library can print students and school residents to always be familiar with the activities of reading, understanding, and understanding the purpose of an information and science, and produce quality work in order to improve the quality of education. So in the end the achievement was relatively easy to achieve. This study aims to know about the management of library management related to management functions such as: planning, organizing, leadership, and controlling in SMAN 1 Janapria. This research is qualytative research, data collecting technique in this research is done by interview, observation and documentation. The data processing procedure is done by triangulation technique, checking informant, and examination of data.